A Simple Synthetic Route to Obtain Pure Trans‐Ruthenium(II) Complexes for Dye‐Sensitized Solar Cell Applications. Issue 11 (7th August 2013) - Barolo, Claudia; Yum, Jun‐Ho; Artuso, Emma; Barbero, Nadia; Di Censo, Davide; Lobello, Maria Grazia; Fantacci, Simona; De Angelis, Filippo; Grätzel, Michael; Nazeeruddin, Mohammed Khaja; Viscardi, Guido
Abstract We report a facile synthetic route to obtain functionalized quaterpyridine ligand and its trans‐dithiocyanato ruthenium complex, based on a microwave‐assisted procedure. The ruthenium complex has been purified using a silica chromatographic column by protecting carboxylic acid groups as iso‐butyl ester, which are subsequently hydrolyzed. The highly pure complex exhibits panchromatic response throughout the visible region. DFT/time‐dependent DFT calculations have been performed on the ruthenium complex in solution and adsorbed onto TiO2 to analyze relative electronic and optical properties. The ruthenium complex endowed with the functionalized quaterpyridine ligand was used as a sensitizer in dye‐sensitized solar cell yielding a short‐circuit photocurrent density of more than 19 mA cm−2 with a broad incident photon to current conversion efficiency spectra ranging from 400 to 900 nm, exceeding 80 % at 700 nm.